2021
DOI: 10.31949/educatio.v7i2.1074
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Problem Based Learning untuk Meningkatkan Minat dan Hasil Belajar Managemen Operasional di Masa Pandemi Covid-19

Abstract: Penelitian ini dilatarbelakangi rendahnya minat dan hasil belajar mahasiswa pada mata kuliah managemen operasional di masa pandemi covid-19. Tujuan penelitian ini untuk mengetahui peningkatan minat dan hasil belajar managemen operasional di masa pandemi covid-19. Penelitian ini dilakukan pada mahasiswa di Prodi Managemen STIE Semarang Tahun Akademik 2020/2021. Jenis penelitian ini penelitian tindakan kelas  yang terdiri dari siklus 1 dan siklus 2. Masing-masing siklus terdiri dari perencanaan, pelaksanaan, obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…The same research, problem-based learning models can improve student motivation and learning outcomes [19]. The same study showed an increase in operational management learning outcomes during the Covid-19 pandemic that using the Problem Based Learning method can increase student interest and learning outcomes [20]. In addition, states that students do learn more actively in all four phases of problem-based learning [17].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The same research, problem-based learning models can improve student motivation and learning outcomes [19]. The same study showed an increase in operational management learning outcomes during the Covid-19 pandemic that using the Problem Based Learning method can increase student interest and learning outcomes [20]. In addition, states that students do learn more actively in all four phases of problem-based learning [17].…”
Section: Introductionmentioning
confidence: 82%
“…They are more creative, appear confidently quite well, and are better able to communicate and work together in solving problems. Some studies that show the implementation of problem-based learning are as follows: Problembased learning improves student activity and problemsolving skills of junior high school students [18], increases motivation and learning outcomes of civic education for junior high school students [19], increases student interest in implementing operations [20], improve active attitudes, self-confidence and communication of high school students [17], improving understanding in IPA [21]. Research that has been carried out shows that improving problemsolving skills with the PBL model strategy will make students more active in learning science to find solutions to real-world problems easily.…”
Section: Introductionmentioning
confidence: 99%
“…Pendapat Siti Aniqoh mengatakan bahwa pelajar perlu untuk melibatkan tindakan dan mental dalam diri sendiri karena ada beberapa hal yang mampu bukan hanya diberitahukan. Serta hasil dari apa yang disampaikan, itulah keaktifan yang merupakan langka-lanngkah belajar yang di desain supaya siswa merasa gembira, mendudkung kegiatan itu sehingga keterlibatan siswa dengan menggunakan metode belajar aktif ini akan menarik minat siswa (Shofwani and Rochmah 2021). Siswa juga bisa menyelesaikan tugasnya sesuai dengan apa yang mereka ketahui dalam otak mereka dan tak kalah penting siswa dapat menyelesaikan masalah dalam dirinya sendiri.…”
Section: Pendahuluanunclassified
“…Review of the literature on the subject revealed that it was seen that many experimental researches (Deveci, 2002;Arıcı, 2021;Çanakçı, 2021;Dita et al, 2021;Foo et al, 2021;Ghani et al, 2021;Hasanah et al, 2021;Lestari et al, 2021;Ilma et al, 2021;Putri and Sundayana, 2021;Sari et al, 2021;Shofwani and Rochmah, 2021;Simanjuntak et al, 2021;Suparman et al, 2021;Fong et al, 2022;Kim et al, 2022;Putri et al, 2022;Safitri et al, 2022;Tanrıkulu, 2022;Trullas et al, 2022) were conducted on PBL. It was determined that the researches in the literature focused on determining the effectiveness of PBL in different subjects and comparing it with various learning approaches.…”
Section: Introductionmentioning
confidence: 99%